Implementation of Integrated Accounting Information Systems in Higher Education: Evidence from Muhammadiyah University of Semarang - Siti Amanah; Dista Amalia Arifah (Universitas Muhammadiyah Semarang, 2026)
This study aims to examine the implementation of an integrated accounting information system and its impact on financial reporting efficiency, information quality, and management support in a private Islamic-based university, namely Universitas Muhammadiyah Semarang. The research addresses issues related to fragmented data, delays in financial reporting, and limited coordination across organizational units. A descriptive case study approach was employed, using primary data collected through in-depth interviews and observations involving financial staff, faculty leaders, and information technology personnel, supported by secondary data from institutional documents. The findings indicate that the integrated system has significantly improved the efficiency of financial reporting by accelerating data processing and enhancing real-time access to financial information. In addition, the system has contributed to improved transparency and accountability, although challenges remain in terms of system stability, infrastructure disparities, and user competence. Management support was identified as a critical factor in ensuring successful implementation through policy direction, budget allocation, and technological development. Overall, the study highlights that the success of accounting information systems depends not only on technological quality but also on organizational readiness and continuous adaptation strategies.